Coagulation Activation Markers in the Prediction of Venous Thrombosis after Elective Hip Surgery - Cofrancesco, E; Cortellaro, M; Corradi, A; Ravasi, F; Bertocchi, F (Thrombosis and Haemostasis, 1997)
Background. Despite prophylaxis, deep vein thrombosis (DVT) after hip surgery continues to occur frequently. Thus it would be helpful if before surgery patients at higher risk of DVT could be identified and more adequate prophylaxis given. As part of an international study on the prevention of DVT after total hip replacement, we investigated whether preoperative levels of three coagulation activation markers, prothrombin fragment F1+2 (F1+2), thrombin-antithrombin III complexes (TAT) and D-dimer, correlate with results of postoperative venography.Methods. 159 patients undergoing total hip replacement were randomized to receive 10, 15 or 20 mg desirudin bid or 5000 IU unfractionated heparin tid immediately before surgery and then for 11 days, until bilateral venography was performed. Preoperative F1+2, TAT and D-dimer plasma levels were measured using ELISA procedures. As no difference among anticoagulant treatments or in the interaction between treatments and DVT was detected for any of the three variables, results are reported as pooled data.Findings. The frequency of DVT was 18.8% in the low (0.75-1.33 nM) vs 65.7% in the high third of distribution (1.77-3.47 nM) of F1+2 (p ˂.001), 27.3% in the low (2.00-2.50 μg/1) vs 57% in the high third (5.10-61.00 μg/l) of TAT (p = .042), and 29.4% in the low (39-59 μg/1) vs 57.1% in the high third (129-651 μg/1) of D-dimer (p = .051).Interpretation. Preoperative F1+2, TAT and D-dimer levels are associated with the risk of development of DVT after total hip replacement.